Peran Mata Pelajaran PKn dalam Mengembangkan Karakter Nasionalisme di Sekolah Dasar - Ratnawati, Dewi; Hanifah, Nurdinah; Kurnia, Dadang (Jurnal Pena Ilmiah, 2021)
Civics is one of the compulsory subjects taught in formal education programs in Indonesia from elementary to undergraduate level. Given that in its role, Civics is expected to be a bridge to develop good character values in students, one of which is the character of nationalism. The method used in this study is a qualitative descriptive method, the research subjects are teachers and students of Class V SDN Jatisura III. The findings in this study are in the implementation of learning, the teacher makes habits for students to always carry out positive activities such as reading prayers before studying and carrying out ceremonial activities. However, due to the Covid-19 pandemic,the teacher implements social activities as an alternative in the form of social activities such as visiting friends who are affected by disasters and distributing masks. The obstacles that arise in the implementation of Civics learning are caused by environmental and technological factors. Teacher responseRegarding the role of Civics in developing the character of nationalism, the teacher shows that Civics is a compulsory subject that must be taught.